The Influence of Leadership and Motivation on The Performance of Islamic Instructors in West Sulawesi Province - Jalal Jalal; Wahda Rasyid; Bambang Deliyanto (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: To analyze the influence of leadership and motivation on the performance of Islamic religion instructors in West Sulawesi province. Design/methodology/approach: This research was conducted by involving as many as 125 Islamic religious staff who were civil servants at the office of the Ministry of Religion of West Sulawesi province as respondents. Leadership and motivation are independent variables in this study. Meanwhile, performance is the dependent variable, besides motivation, it is an intermediary variable, the leadership variable, and the performance variable. Findings: The equation that can be formed from the results of the analysis is: Y = 0.22 X1 + 0.75 X2, where Y is performance and X1 is leadership and X2 is motivation. Leadership has a positive and significant effect on the performance of Islamic instructor workers as indicated by the path coefficient at 0.22 with a p-value less than 0.01. Similarly, leadership and significant positive effect on the motivation of 0.89 with a p-value of less than 0,01. Motivation has a positive and significant effect on the performance of religious educators with a value of 0.75 with a p-value less than 0.01. Leadership and motivational variables together influence the performance variable by 66, 7 % with a p-value smaller than at 0.05. In the mediation test with the Sobel test, the Z count is 10.963024, much greater than the Z table value of 1.96, which means that the motivation variable significantly mediates the relationship between the leadership and performance variables. The suggestion that the researcher can give to the Ministry of Religion of West Sulawesi province is to increase the quality of leadership by improving several things, especially the dimensions of personal attention, this can be developed by fostering respect for subordinates and creating more harmonious relationships, motivating to work more creatively and innovatively. Should always be listened to, as well as training extension workers to increase cooperation among other extension agents in completing missions carried out by the ministry of religion. Practical implications: the recommendations of this study can serve as guidelines for improving the performance of Islamic religious extension agents in the ministry of religion in general... Originality/value: This research is original and was conducted in West Sulawesi province from September to November 2020. Paper type: Research paper